PERAN INTERNATIONAL COMMITTEE OF THE RED CROSS (ICRC) DALAM MENANGANI PEREKRUTAN TENTARA ANAK DI SOMALIA TAHUN 2012-2016 - Ade Maitsya Putri; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to explain the issue of Recruitment of child soldiers in Somalia 2012-2016, explaining the role of the International Committee Of The Red Cross (ICRC) in handling the recruitment of child soldiers in Somailia Year 2012-2016, as well as to know the obstacles or constraints International Committee Of The Red cross (ICRC) in performing its role.The method applied in this research is the description, which will illustrate how the war of a Non-Governmental Organization (NGO). This research is structured using International Organizational theory, and the concept of the role of international organization, pluralist perspective.Level of behavioral analysis of organizational groups with traditional institutional and legal approaches to the approach to empirical dynamics. The technique of data collection is through Library research technique.The results of this study indicate that the ICRC plays an important role in humanitarian law in dealing with the recruitment of child soldiers that are very much found in Africa, especially the Somali State. The ICRC carries out its functions as an implementer of humanitarian operations, regulators, , and disseminators of norms, and acts as a socialization agent for humanitarian principles concerned with the recruitment of child soldiers in both war and after the war.Keywords: Somalia, child soldiers, ICRC